Level of Motor Skills of Students Participating in Extracurricular Football Activities at State Junior High School Negeri 1 Depok, Sleman Regency - Amarta, Muhammad Fajar; Yuliarto, Hari; Ngatman; Akbar, Claudio Fadia (Indonesian Journal of Sport Management, 2025)
Motor skills, both gross and fine, form the basis for performing daily physical activities while also supporting students' academic and non-academic achievements. In this context, extracurricular sports activities particularly soccer hold strategic potential in enhancing students' motor skills through systematic and structured training. To determine the level of motor skills of students participating in extracurricular soccer activities at State Junior High School 1 Depok. This research design is a quantitative descriptive research design. It uses a survey method with testing and measurement techniques to obtain data. The research population consists of 23 students participating in extracurricular soccer activities at State Junior High School 1 Depok. This study uses the Barrow Motor Ability Test, which consists of six test items: standing broad jump, wall pass, zig-zag run, medicine ball put, soft ball throw, and 60-yard dash. The results of the study on the motor skills of extracurricular soccer students at State Junior High School 1 Depok are as follows: 0 students were in the very high category, 9 students (39.1%) were in the high category, 9 students (39.1%) were in the moderate category, 5 students (21.7%) were in the low category, and 0 students were in the very low category. The results of this study can be used as a guide for soccer coaches or extracurricular advisors at State Junior High School 1 Depok to select players with good motor skills who will later participate in school and district-level soccer events